Visible tumor surface response to physical plasma and apoptotic cell kill in head and neck cancer. Issue 9 (September 2016) - Schuster, Matthias; Seebauer, Christian; Rutkowski, Rico; Hauschild, Anna; Podmelle, Fred; Metelmann, Camilla; Metelmann, Bibiana; von Woedtke, Thomas; Hasse, Sybille; Weltmann, Klaus-Dieter; Metelmann, Hans-Robert
Abstract: The aim of the study was to learn, whether clinical application of cold atmospheric pressure plasma (CAP) is able to cause (i) visible tumor surface effects and (ii) apoptotic cell kill in squamous cell carcinoma and (iii) whether CAP-induced visible tumor surface response occurs as often as CAP-induced apoptotic cell kill. Twelve patients with advanced head and neck cancer and infected ulcerations received locally CAP followed by palliative treatment. Four of them revealed tumor surface response appearing 2 weeks after intervention. The tumor surface response expressed as a flat area with vascular stimulation (type 1) or a contraction of tumor ulceration rims forming recesses covered with scabs, in each case surrounded by tumor tissue in visible progress (type 2). In parallel, 9 patients with the same kind of cancer received CAP before radical tumor resection. Tissue specimens were analyzed for apoptotic cells. Apoptotic cells were detectable and occurred more frequently in tissue areas previously treated with CAP than in untreated areas. Bringing together both findings and placing side by side the frequency of clinical tumor surface response and the frequency of analytically proven apoptotic cell kill, detection of apoptotic cells is as common as clinical tumor surface response. There was no patient showing signs of an enhanced or stimulated tumor growth under influence of CAP. CAP was made applicable by a plasma jet, kINPen ® MED (neoplas tools GmbH, Greifswald, Germany).